Effectiveness and User Satisfaction of an ePRO-Based mHealth Application for Near Miss Reporting and Patient Safety Culture in the ICU - Lilis Suryani (STIKep PPNI Jawa Barat, 2025)
Background: Near miss reporting and patient safety culture are critical to quality improvement in intensive care units (ICUs), yet conventional reporting systems are often constrained by underreporting, delayed submission, and limited feedback. Mobile health (mHealth) applications integrated with electronic patient-reported outcomes (ePRO) offer a promising approach to facilitate real-time reporting and strengthen safety culture in high-risk clinical environments. Objective: This study evaluated the effectiveness and user satisfaction of an ePRO-based mHealth application in improving near miss reporting and patient safety culture in ICU settings. Methods: A mixed-methods study was conducted in the ICU of a level B hospital in Karawang, Indonesia, involving 250 healthcare workers, primarily nurses. The intervention was implemented over six months using a user-centered design approach. Outcomes included near miss reporting rates, reporting timeliness, and Hospital Survey on Patient Safety Culture (HSOPSC) scores. Quantitative data were analyzed using paired t-tests and multiple linear regression, while user satisfaction and implementation experiences were explored using the System Usability Scale (SUS) and focus group discussions. Results: Near miss reporting increased 2.3-fold after implementation, and timely reporting within one hour rose from 21.4% to 68% (p < 0.001). Significant improvements were observed in patient safety culture domains, particularly non-punitive response to error and communication openness. User satisfaction was high, with a mean SUS score of 82.3. Technical challenges and initial staff resistance were identified as key barriers. Conclusion: The ePRO-based mHealth application significantly improved near miss reporting, enhanced patient safety culture, and demonstrated high usability in ICU settings. Despite technical and cultural challenges, the intervention aligns with the WHO Global Patient Safety Action Plan 2021–2030 and underscores the importance of integrating digital innovation with safety culture initiatives in resource-limited healthcare systems